BETWEEN DATA AND MEANINGS: EPISTEMOLOGICAL AND METHODOLOGICAL CONTRIBUTIONS OF ARTIFICIAL INTELLIGENCE TO QUALITATIVE AND QUANTITATIVE RESEARCH (REMUNOM, 2026)
The incorporation of Artificial Intelligence (AI) into the field of scientific research has generated debates regarding its actual methodological, epistemological, and ethical contributions, especially with respect to qualitative and quantitative research. In this context, this article raises the following problem: how can AI contribute to the improvement of methodological processes in scientific research without compromising intellectual autonomy, critical interpretation, and the ethical principles of the researcher? The objective is to critically analyze the potentialities, limitations, and ethical implications of using AI in the production of scientific knowledge. Methodologically, this is an integrative literature review with a qualitative, exploratory, and descriptive approach, grounded in classical and contemporary authors who discuss technology, scientific methodology, and artificial intelligence. The results indicate that AI significantly enhances the capacity for data collection, organization, processing, and analysis, promoting greater analytical accuracy, time optimization, and diversification of interpretative strategies. Tools such as ChatGPT, IRAMUTEQ, and Jamovi are configured as cognitive mediators, capable of supporting researchers in both qualitative and quantitative analyses without replacing human judgment. As an original contribution, the study proposes understanding AI as a complementary methodological device, whose use requires a critical, reflective, and ethical stance. It is concluded that the balanced integration between human and artificial intelligence inaugurates a new paradigm in contemporary scientific research, guided by innovation, interdisciplinarity, and methodological rigor.